2014
DOI: 10.1002/anie.201404133
|View full text |Cite
|
Sign up to set email alerts
|

Hexacoordinate Nickel(II)/(III) Complexes that Mimic the Catalytic Cycle of Nickel Superoxide Dismutase

Abstract: A functional model complex of nickel superoxide dismutase (NiSOD) with a non-peptide ligand which mimics the full catalytic cycle of NiSOD is unknown. Similarly, it has not been fully elucidated whether NiSOD activity is a result of an outer- or inner-sphere electron-transfer mechanism. With this in mind, two octahedral nickel(II)/(III) complexes of a bis-tridentate N2 S donor carboxamide ligand, N-2-phenylthiophenyl-2'-pyridinecarboxamide (HL(Ph)), have been synthesized, structurally characterized, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“… 11 − 13 Over the past two decades, many high-valent metal complexes have been studied to gain fundamental insights into the structural, functional and mechanistic aspects of the enzymes and their counterparts. 14 17 Detailed mechanistic studies have shown that ET occurs through either inner-sphere or outer-sphere mechanisms and the M–O 2 •– species is an important reactive intermediate formed via the inner-sphere mechanism. 18 However, another class of effective inhibitors of ROS are antioxidants that are purely organic molecules.…”
mentioning
confidence: 99%
“… 11 − 13 Over the past two decades, many high-valent metal complexes have been studied to gain fundamental insights into the structural, functional and mechanistic aspects of the enzymes and their counterparts. 14 17 Detailed mechanistic studies have shown that ET occurs through either inner-sphere or outer-sphere mechanisms and the M–O 2 •– species is an important reactive intermediate formed via the inner-sphere mechanism. 18 However, another class of effective inhibitors of ROS are antioxidants that are purely organic molecules.…”
mentioning
confidence: 99%
“…Thee lectronic absorption spectrum of 1 Cl in CH 3 CN features bands at l max /nm (e/m À1 cm À1 ) = 912 (26), 550 sh (65), 323 (20 576), 294 (17 670) and 237 sh (32 750) comparable to those of reported octahedral Ni II complexes. [22][23][24] Thes low evaporation of aC H 3 CN/CH 2 Cl 2 solution of 1 Cl afforded crystals suitable for X-ray diffraction. TheX -ray structure of 1 Cl revealed it to be am onomer (Figure 1, top [23,24] but is % 0.07 longer than that of the MCR ox1-silent state of the enzyme where the Ni II has N 4 SO coordination and the Ni II -S CoM distance is 2.40 .…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] Thes low evaporation of aC H 3 CN/CH 2 Cl 2 solution of 1 Cl afforded crystals suitable for X-ray diffraction. TheX -ray structure of 1 Cl revealed it to be am onomer (Figure 1, top [23,24] but is % 0.07 longer than that of the MCR ox1-silent state of the enzyme where the Ni II has N 4 SO coordination and the Ni II -S CoM distance is 2.40 . [25] TheS ÀSd istance of 1 Cl is in the range of typical SÀSd istances found with Ar-S-S-Ar disulfides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[46][47] The role of the fifth ligand in the axial position to stabilize the Ni III oxidation state has been also reproduced. 35,[41][42] However, the great majority of the low-molecular weight synthetic Ni II complexes, despite their apparent appropriate redox properties for SOD activity, are not active as catalysts even if they can mimic the partial [40][41] or full 48 catalytic cycle under stoichiometric conditions. Their lack of reactivity has often been rationalized either by their sensitivity to the superoxide or derivatives, or by the irreversibility of the Ni III /Ni II redox process.…”
Section: Scheme 1 Active and Catalysed Reaction Centre By The Nisodmentioning
confidence: 99%